Analisis Kesuksesan Sistem Informasi Website Pemerintah Kabupaten Pamekasan Berdasarkan Model Delone and Mclean - Belly Purna Bahesa; Vivine Nurcahyawati; Yoppy Mirza Maulana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
As more and more areas implement information technology in the field of e-government, evaluation of its effectiveness is an increasingly important topic for practitioners and researchers. After an information system enters the implementation phase in the life cycle of information system development, it is necessary to conduct post-implementation review. Pamekasan District Government website is part of internet-based information technology services managed by KOMINFO Pamekasan District. Since the website published by the government has never conducted an analysis of the success of information systems to the Pamekasan District Government Website. Based on the results of research on success analysis Pamekasan District Government website based on DeLone and McLean model that has been done and resulted in two drop between variables. The first, indicates that the quality of information available on the website of the Government of Pamekasan Regency is good enough to affect user satisfaction. And the second, indicating that some of the respondents said the website is good and comfortable to use so that users feel comfortable to access it again.